Implementación de un sistema de control de postura y velocidad en el patinaje de velocidad basado en procesamiento de imágenes - González González, Deysi Tamara (2023)
This research presents developing and implementing a posture and speed control system for speed skating using artificial vision. The project was carried out in four phases: including the search and analysis of information, development, and implementation of the system, and analysis of the data obtained to determine the effectiveness of the system. It was carried out in the school "Chimborazo Skate," with three intermediate skaters trained with the system for four weeks, obtaining data on posture, technique, speed, time, and resistance before and after the system. The system consists of two stages; in the first one, artificial vision techniques were used to detect the skater's posture and notify in case of a bad one. In the second, it also used artificial vision techniques to measure the skater's speed on the track. For this reason, the video acquisition is through the camera of the DJI Tello drone; the information is sent by a Wi-Fi connection to the system developed for processing. Proving that the system improves the skater's performance both in speed and posture, sustaining to be an efficient tool for training in speed skating. The statistical analysis results show that the skaters' median speed before the system was 7.286m/s, and after the system was 7.852m/s. As for posture, it was obtained that before the system, they adopted a good posture, and after the system, they achieved an excellent posture